Demand analysis of general practice patients for teaching clinic based on Kano model - Chen, Zhiqian; Yin, Ankang; Wang, Yi (Frontiers in Public Health, 2024)
Background General practice teaching clinics play a crucial role in the training of general practitioners, as they are more likely to enhance reception skills compared to traditional training methods. The quality of teaching clinics is largely determined by the level of patient acceptance. In recent years, the Kano model has become increasingly popular in the healthcare industry and has been used to enhance patient satisfaction. The objective of this study is to apply the Kano model to investigate the needs of patients in general practice teaching clinics and to rank the significance of each demand. This study will serve as a reference for enhancing the service quality of teaching clinics and advancing the field of general practice. Methods A total of 101 patients of general practice at the Affiliated Hospital of Yangzhou University in Jiangsu province were selected using a random convenience sampling method to participate in a questionnaire survey. The questionnaire was designed by members of our team and was based on the Kano model. The study defined the service demand, assessed the impact of both satisfaction and dissatisfaction and created a matrix bubble diagram. Results The study findings revealed that out of the 14 items of the general practice teaching clinic service demands, 1 item was categorized as a must-be requirement, 4 items were categorized as one-dimensional requirements, 2 items were categorized as an attractive requirement, 2 items were categorized as an indifferent requirement, and 5 items were categorized as mixed attributes. The findings of the matrix analysis showed that 4 items were situated in the area of one-dimensional attributes quadrant, 3 items were situated in the area of attractive attributes quadrant, 5 items were situated in the area of indifferent attributes quadrant, and 2 items were situated in the area of must-be attributes quadrant. Conclusion The patients of general practice have positive attitudes toward teaching clinics. The findings can offer valuable insights for enhancing the quality of service and patient experience in general practice teaching clinics as well as for advancing the field of general practice.